1998
DOI: 10.1002/jor.1100160413
|View full text |Cite
|
Sign up to set email alerts
|

Local tissue properties in bone healing: Influence of size and stability of the osteotomy gap

Abstract: To characterize the site-specific mechanical and histological properties in fracture repair and to relate these properties to the initial mechanical situation, an experimental fracture model was used in the metatarsus of 42 sheep. The mechanical situation of a transverse osteotomy was described by three gap sizes (1, 2, or 6 mm) and two amounts of strain (7 or 31%). An external fixator that allowed a defined axial movement provided control of these settings. Nine weeks following surgery, the healing area was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 176 publications
(102 citation statements)
references
References 22 publications
2
96
0
4
Order By: Relevance
“…These results confirm former studies demonstrating that the mechanical stability of the fracture healing zone is determined not only by callus size, but also by the local mechanical properties inside the callus. 20,21 In both cases, secondary healing occurred with a mixture of intramembranous and enchondral ossification, indicating that the rigid fixator was not sufficiently stiff to provoke exclusively direct ossification. Furthermore, a maximum flexible condition with the bone fragments probably coming into contact during the initial postoperative phase did not induce a nonunion, confirming the hypothesis of Gröngröft et al…”
Section: Discussionmentioning
confidence: 96%
“…These results confirm former studies demonstrating that the mechanical stability of the fracture healing zone is determined not only by callus size, but also by the local mechanical properties inside the callus. 20,21 In both cases, secondary healing occurred with a mixture of intramembranous and enchondral ossification, indicating that the rigid fixator was not sufficiently stiff to provoke exclusively direct ossification. Furthermore, a maximum flexible condition with the bone fragments probably coming into contact during the initial postoperative phase did not induce a nonunion, confirming the hypothesis of Gröngröft et al…”
Section: Discussionmentioning
confidence: 96%
“…Likewise Charnley [21] stated that osteogenesis is actually stimulated by compression of the fragments. It is generally accepted that reduction and fixation of the fracture to align the fragments in contact, promotes bone healing [22]. A direct correlation between the fracture gap width and the healing process is given in the literature; Large fracture gaps more than 2 mm cause a delay in fracture healing, due to large amount of cartilage and external callus formation between the fracture fragments as demonstrated in Graph 3 Post-operative evaluation (Biting Efficiency) experimental [23], and clinical investigations [24].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical environment can be characterized by the fracture gap size and by the interfragmentary movement. Several studies have demonstrated that an increasing gap site results in a delay of healing [4,10]. Also excessive motion at the fracture size induces callus formation but retards the consolidation process of the callus [5,20,27].…”
Section: Discussionmentioning
confidence: 99%